Seemingly Senseless Acts: Who and When - Stagnaro, Michael Nicholas (Journal for the cognitive science of religion, 2022)
In the book Ritual: How Seemingly Senseless Acts Make Life Worth Living, Dimitris Xygalatas walks the reader through what the social/cognitive sciences can teach us about the underlying function of ritual, and why it has persisted as an enduring feature of the human species. This thoughtful book covers a wide range of topics but mostly stays quiet on providing the reader with some understanding of what predicts ritual practice within communities. In this paper, we take the insights provided by Xygalatas throughout the book and attempt to construct several categories based on the core functions that ritual provides. Then, using a nationally representative sample of 1,000 U.S. participants, we attempt to test several of the predictions that come out of the book, finding support for some claims, while finding little to none for others.